Fibroblast growth factor 5 overexpression ameliorated lipopolysaccharide-induced apoptosis of hepatocytes through regulation of the phosphoinositide-3-kinase/protein kinase B pathway. Issue 23 (5th December 2022) - Cui, Shengyu; Li, Yuhua; Zhang, Xutao; Wu, Bing; Li, Ming; Gao, Jixian; Xu, Lin; Xia, Hao
Abstract: Background: Sepsis is a systemic inflammatory syndrome induced by several infectious agents. Multiple organs are affected by sepsis, including the liver, which plays an important role in metabolism and immune homeostasis. Fibroblast growth factors (FGFs) participate in several biological processes, although the role of FGF5 in sepsis is unclear. Methods: In this study, lipopolysaccharide (LPS) was administrated to mice to establish a sepsis-induced liver injury. A similar in vitro study was conducted using L-02 hepatocytes. Western blot and immunohistochemistry staining were performed to evaluate the FGF5 expression level in liver tissues and cells. Inflammatory cell infiltrations, cleaved-caspase-3 expressions, reactive oxygen species and levels of inflammatory cytokines were detected by immunofluorescence, dihydroethidium staining, and reverse transcription quantitative polymerase chain reaction analysis, respectively. Flow cytometry was used to detect the apoptosis level of cells. In addition, ribonucleic acid (RNA)-sequencing was applied to explore the possible mechanism by which FGF5 exerted effects. Results: LPS administration caused FGF5 down-regulation in the mouse liver as well as in L-02 hepatocytes. Additionally, with FGF5 overexpression, liver injury and the level of hepatocyte apoptosis were ameliorated. Further, RNA sequencing performed in hepatocytes revealed the phosphoinositide-3-kinase/protein kinase B (PI3K/AKT) pathway as a possible pathway regulated by FGF5 . This was supported using an inhibitor of the PI3K/AKT pathway, which abrogated the protective effect of FGF5 in LPS-induced hepatocyte injury. Conclusion: The anti-apoptotic effect of FGF5 on hepatocytes suffering from LPS has been demonstrated and was dependent on the activation of the PI3K/AKT signaling pathway.